IMPLEMENTASI STATISTICAL PROCESS CONTROL (SPC) DAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) PADA PROSES PRODUKSI SHEET FILM DI PERUSAHAAN PET FILM - Ramadhania, Sherin; Susilo, Diyan; Hanan, Siti (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
PT. ABC faces a quality control issue with a defect rate of 5.5%, resulting in customer complaints. This study aims to identify the types of defects in sheet film products, analyze their root causes, and evaluate quality control measures to reduce defects. The research uses Statistical Process Control (SPC) to monitor the production process and Failure Mode and Effect Analysis (FMEA) to analyze potential failures in the production system. The SPC analysis revealed that the most frequent defects were ILK Defect (501 rolls), followed by Thickness Defect (188 rolls) and Scratch Defect (100 rolls). The root causes of defects were identified using a fishbone diagram, which pointed to Method, Material, Machine, and Man as the main factors. FMEA results indicated that the primary cause of defects was an issue with the hopper on the machine, which caused material transfer delays, leading to V-ILK and Thickness Defects. This study recommends improving machine maintenance, revising operational procedures, and enhancing operator training to reduce defects and improve product quality